Strength Design of Compressed Reinforced Concrete Elements by Deformation Method Based on Extreme Criterion - Shkurupiy, Oleksandr; Lazariev, Dmytro; Davydenko, Yurii (International Journal of Engineering and Technology, 2018)
Investigations of the normal sections strength of compressed elements using a deformation method were performed. The shape of the section, the class of concrete and the percentage of reinforcement were taken into account when performing analytical calculations. Analytical, numerical, optimization techniques etc. were used for solving of this task. The results of the analytical calculations and the data of the experimental studies were compared.Â Â